The Impact of Project-Based Learning on Students’ Creative Self-Efficacy in Statistics Learning - Novianti, Suci Tiara; Sri Winarni; Marlina (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Statistics learning at the junior high school level still faces challenges in developing students’ creative thinking skills. Students often struggle to understand fundamental statistical concepts due to conventional instructional practices that provide limited opportunities for in-depth data exploration. This study aims to analyze the effect of implementing the Project-Based Learning model on the Creative Self-Efficacy of eighth-grade students at SMPN 11 Jambi City in the topic of statistics. Employing a quantitative approach, this research utilized a true experimental method with a posttest-only control group design. This design was selected to avoid testing effects and to focus on the final learning outcomes. The study involved two sample classes: an experimental class that applied Project-Based Learning and a control class that received Direct Instruction. Research instruments included an observation sheet to measure the implementation of the learning model and a Likert-scale Creative Self-Efficacy questionnaire to assess the dependent variable. Data were analyzed using the Kolmogorov-Smirnov normality test, Levene’s homogeneity test, and an independent sample t-test. The results revealed a significant effect of Project-Based Learning on students’ Creative Self-Efficacy, with a significance value of 0.002 < 0.05. Furthermore, the experimental class achieved a higher mean posttest score (81.03) compared to the control class (75.17). These findings contribute to the development of instructional strategies that foster students’ creative self-confidence through authentic and meaningful project-based learning experiences.